(3GdEbJUGO GdSjGSj dMeGjI Mbhb GdedcjI GdacQjI aj Xd GJaGb GdJQHS(BTRIPS /s - (3YHO GdNGdb, GdSjO CMeOs ((3GdEScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI(B, s, 2006)
(3fHPI Yf JWhQ MeGjI Mbhb GdedcjI GdacQjI(B- (3NUGFU MeGjI Mbhb GdedcjI GdacQjI aj GWGQ GdJQHS(BTRIPS- (3OhGaY YhdeI MeGjI Mbhb GdedcjI GdacQjI(B- (3MeGjI Mbhb GdedcjI GdacQjI hGdefGaSI GdYGdejI(B- (3MeGjI Mbhb GdedcjI GdacQjI hGdHMK GdYdej hGdEHJcGQ(B- (3MeGjI Mbhb GdedcjI GdacQjI hGdESJKeGQ GdCLfHj(B- (3MeGjI Mbhb GdedcjI GdacQjI hfbd GdJcfhdhLjG(B- (3MeGjI Mbhb GdedcjI GdacQjI hGdJfejI GdRQGYjIs
Keywords: (3GdEbJUGO GdSjGSjs; (3GdedcjI GdacQjIs; (3HQGAI GdENJQGYs